PO123 Thc:cbd (nabiximols) has a beneficial effect on multiple sclerosis related spasticity and delays the need for intrathecal baclofen. (1st December 2017) - Trane, Stefania De; Buchanan, Katrina; Keenan, Liz; Valentine, Claire; Liddicut, Michelle; Stevenson, Val; Farrell, Rachel
Abstract : Objective: Evaluate the efficacy of THC:CBD (Nabiximols) for resistant MS-related spasticity (MS-rs). Background: Spasticity is a problematic symptom in MS. THC:CBD is a second line agent for MS-rs in people presenting side effects (SEs) or inadequate response to other treatments. Design/Methods: Patients failing ≥2 treatments for spasticity were offered THC:CBD. Outcomes were measured at baseline. At 2 weeks telephone review was conducted and at 4 weeks face to face review.Responders continued medication for 3 months and were reviewed at 6 monthly intervals therafter. Spasticity Numerical Rating-Scale (NRS), Multiple Sclerosis Spasticity Scale-88 (MSSS-88), walking ability, concomitant medications and side effects (SE) were recorded. Clinical Responders (CR) were defined as having a≥20% reduction in NRS score, Non Responders (NR) were offered alternative options including Intrathecal Baclofen (ITB). Results: 102 subjects were treated, 24 discontinued THC:CBD within 2 weeks, 78 attended 4 week review. 32%were CRs with improvement in NRS (p<0.001) and MSSS-88 score (p<0.001). Mean time to discontinuation was 3.8 months. Other benefits included improvement in spasms, pain, bladder control and sleep. SEs were reported and mild in 48% and serious in 7%. ITB was pursued in 24 patients. Conclusions: THC:CBD provided symptomatic relief in a significant number of patients and can serve as alternative to ITB.